Kelayakan Usahatani Rumput Laut di Desa Jungutbatu Kecamatan Nusa Penida Kabupaten Klungkung - WIJAYA, I GEDE OPA PIDIA PALGUNA; DJELANTIK, ANAK AGUNG AYU WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Feasibility of Seaweed Farming in Jungutbatu Village, Nusa Penida District, Klungkung Regency. The development of seaweed in Jungutbatu Village faces challenges from the tourism sector which has forced many farmers to change professions and tourism waste has reduced the quality of seawater. The purpose of this research is to 1) analyze the feasibility of seaweed farming, 2) analyze the constraints of seaweed farming after the pandemic 3) analyze the existence of seaweed farming with the tourism sector in Jungutbatu Village, Nusa Penida District, Klungkung Re gency. The sample of this research is 42 farmers. The data in this study were obtained through interviews and observation. The data obtained were analyzed using the analysis of Revenue Cost ratio (R/C ratio) and Qualitative Descriptive. The results showed that seaweed farming cultivated by Jungutbatu Village farmers with an average area of 20 acres was feasible to develop with an R/C ratio of 3.39, the obstacles faced were seed damage, decreased sea water quality and marketing constraints due to lack of knowledge. farmers for the seaweed market, as well as seaweed farming in Jungutbatu Village, Nusa Penida District, Klungkung Regency lost its existence to tourism among productive age groups but still exists among non-productive age groups due to the skills possessed by the community. Advice to farmers to maintain and develop seaweed farming and increase knowledge related to marketing because it has good prospects. For the government to monitor and support seaweed farmers to develop their farming so they can produce products with added value.